1990
DOI: 10.1073/pnas.87.21.8227
|View full text |Cite
|
Sign up to set email alerts
|

Azide-resistant mutants of Escherichia coli alter the SecA protein, an azide-sensitive component of the protein export machinery.

Abstract: Escherichia coil azi mutants, whose growth is resistant to millimolar concentrations of sodium azide, were among the earliest E. coil mutants isolated. Genetic complementation, mapping, and DNA sequence analysis now show that these mutations are alleles of the secA gene, which is essential for protein export across the E. coil plasma membrane. We have found that sodium azide is an extremely rapid and potent inhibitor of protein export in vivo and that azi mutants are more resistant to such inhibition. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
244
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(254 citation statements)
references
References 36 publications
9
244
0
1
Order By: Relevance
“…Precursors of polypeptides were enriched by adding 5 mM sodium azide before labeling. Sodium azide inhibits SecA-dependent protein export (12,23). For analysis of in vivo inhibition of protein processing by globomycin, a specific inhibitor of signal peptidase II (18), the antibiotic was added before labeling to a final concentration of 100 ,ug/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Precursors of polypeptides were enriched by adding 5 mM sodium azide before labeling. Sodium azide inhibits SecA-dependent protein export (12,23). For analysis of in vivo inhibition of protein processing by globomycin, a specific inhibitor of signal peptidase II (18), the antibiotic was added before labeling to a final concentration of 100 ,ug/ml.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the F-ATPases, a number of other ATPases are inhibited by azide. They include the ABC transporters (34,35), the preprotein translocase SecA (36,37), DNA topoisomerase II␣ (38), and ecto-ATPases (39,40). In each case, azide probably enhances the inhibitory effect of ADP by stabilizing the ADP-bound state, and this enhancement has been demonstrated for the SecA translocase (41).…”
Section: ͚H͚i͉i(h) ϫ I(h)i͉͚͞h͚ii(h)i Where I(h)mentioning
confidence: 99%
“…This observation suggested that tig inactivation either alleviates the export defect or exposes the presecretory protein to degradation. To distinguish between these two possibilities, we measured the relative half-life of pre-Bla in MC4100 and HDB56 that were treated with sodium azide, an inhibitor of protein export (36). Bla was immunoprecipitated from cells that were pulse-labeled and subjected to either a 0 or 5-min chase.…”
Section: Fig 1 Disruption Of Tig Suppresses the Targeting Factor Rementioning
confidence: 99%